Percutaneous Dilatational Tracheostomy Using Tube Exchanger. (August 2019) - Ronen, Ohad; Gurevich, Alexander; Ivry, Shimon; Altman, Edward; Kukuev, Evgeni
Abstract : We describe a modified technique for percutaneous dilatational tracheostomy using a 15F tube exchanger or Eschmann catheter. A retrospective review of 1180 procedures using this modified technique demonstrated it to be effective with a failure rate of only 0.25% (3 patients). Moreover, it provides an additional safeguard with the ability to rapidly reintroduce the endotracheal tube into the trachea guided by the exchange catheter in the event of accidental extubation during the procedure. This technique needs no additional special devices or equipment (eg, a bronchoscope). However, a prospective study is needed to better define its complication rate.